The Level of VO2 Max With Kizami Tsuki's Punch Speed In Karate Athletes - Sudirman, Sudirman; Hudain, Muh. Adnan; Sahabuddin, Sahabuddin (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study is a correlational descriptive study that aims to determine the relationship between VO2 Max and Kizami Tsuki's Punch Speed in Karate martial arts sports in KKI Dojo H3 athletes. The independent variable in this study is the ability of Cardiovascular, while the dependent variable is Kizame Tsuki's Punch. The population in this study is Makassar City KKI Karate Athletes with a population of 15 people. To obtain the data, researchers used the Bleep Test. The results showed a significant relationship: VO2 Max with the speed of Kisami Tsuki punches on karate athletes KKI dojo H3 Makassar